Divergent Cl- and H+ pathways underlie transport coupling and gating in CLC exchangers and channels - Lilia Leisle; Yanyan Xu; Eva Fortea; Sangyun Lee; Jason D Galpin; Malvin Vien; Christopher A Ahern; Alessio Accardi; Simon Bernèche (eLife, 2020)
The CLC family comprises H+-coupled exchangers and Cl- channels, and mutations causing their dysfunction lead to genetic disorders. The CLC exchangers, unlike canonical 'ping-pong' antiporters, simultaneously bind and translocate substrates through partially congruent pathways. How ions of opposite charge bypass each other while moving through a shared pathway remains unknown. Here, we use MD simulations, biochemical and electrophysiological measurements to identify two conserved phenylalanine residues that form an aromatic pathway whose dynamic rearrangements enable H+ movement outside the Cl- pore. These residues are important for H+ transport and voltage-dependent gating in the CLC exchangers. The aromatic pathway residues are evolutionarily conserved in CLC channels where their electrostatic properties and conformational flexibility determine gating. We propose that Cl- and H+ move through physically distinct and evolutionarily conserved routes through the CLC channels and transporters and suggest a unifying mechanism that describes the gating mechanism of both CLC subtypes.